WORK ETHIC AND MULTIPLE LIVELIHOOD STRATEGIES OF WONOSEWU FOREST FARMERS HOUSEHOLDS IN THE ALAS AREA OF MOUNT BROMO, KARANGANYAR - Wijaya, Mahendra; Marimim; Pujihartati, Sri Hilmi; Sudarsana; Ayu Firda Anisaningtyas, Ninda (SoCul: International Journal of Research in Social Cultural Issues, 2024)
The aim of this study was to explore deeper on Work Ethic and Multiple Livelihood Strategies of Forest Farmers Households of KTH Wonosewu members who live in Sewurejo Village, Mojogedang District, Karanganyar Regency. This research design uses a qualitative approach. The data collection techniques were done using observation, in-depth interviews, documentation, literature study, and fishbone analysis. Data were analyzed using the Interactive method of Miles & Huberman in the form of data reduction, data presentation and conclusion drawing. The findings of this study are that KTH Wonosewu forest farmers have a high work ethic in managing agriculture and implementing a dual livelihood strategy by also working in the livestock sector. The work ethic possessed by KTH Wonosewu forest farmers is shown by future-oriented work motivation, respect for time, and responsibility for their work. The existence of a high work ethic and the efforts made by implementing a dual livelihood strategy, so KTH Wonosewu forest farmers have been able to improve their welfare bit by bit. This research can provide insight into the high work ethic and the application of diversification of income sources to encourage welfare improvement.